Penyebaran orang rumpun Melayu pra-Islam dan perkembangan tulisan bahasa melayu - Shaharir Mohamad Zain, (Universiti Kebangsaan Malaysia, 2003)
The definition of Malay as a race or ethnic group is shrouded in controversy. Thus, it is important for us to understand Malay civilization in the past. With that, one may have a clearer picture of who the Malays are and their history in the past. One aspect of Malay civilization is the evolution of its writing system from Palavi to Kawi and so fort